OCCURRENCE OF FUMONISINS B-1 AND B-2 IN HOMEMADE MEDICINAL PLANTS: EXPOSURE ASSESSMENT IN NORTHERN TURKEY - OMURTAG KORKMAZ, BURCU İREM (AKADEMIAI KIADO ZRT, 2016)
This study was conducted to determine the recent level of contamination with Fumonisin B-1 (FB1) and Fumonisin B-2 (FB2) in major medicinal plants and to assess consumer exposure in northern Turkey. FB1 and FB2 were investigated by using high performance liquid chromatography (HPLC) with fluorescence detection after derivatization with o-phthaldialdehyde (OPA). A total of 78 homemade medicinal plant samples from 14 species were analysed. The recovery in thyme was 67.2 +/- 5.2% for FB1 and 80.8 +/- 14.3% for FB2 spiked with 1 mu g g(-1) of each analyte. The minimum detectable amount for the OPA derivatives of FB1 and FB2 were 1 ng per injection and 2.5 ng per injection, respectively. The limit of quantitation (LOQ) S/N=10 was 0.078 and 0.313 mu g g(-1), and the limit of detection (LOD) S/N=3 was 0.023 and 0.093 mu g g(-1) for FB1 and FB2, respectively. FB1 was detected in thyme (0.125) and mint (0.125 and 0.256 mu g g(-1)) samples; however. FB2 toxin was below the detection limit in all samples. These results indicate that toxins might be present in homemade medicinal plants; however, the risk of exposure to fumonisins by the consumption of those plants was lower than the estimated TDI limits (<2 mu g kg(-1) bw).
Keywords: dietary intake; dried plants; Fusarium toxins; HPLC; CORN; MYCOTOXINS; FOOD; CONTAMINATION; CEREALS; REGIONS; TEA